PENGGUNAAN BAHASA INDONESIA PADA RUANG PUBLIK SEKOLAH DASAR DI KOTA AMBON - Nita Handayani Hasan (Kantor Bahasa Provinsi Gorontalo, 2021)
Indonesian language grammar which applied in poster on school enviorenment has strength to improve students language ability. Therefore, this study aims to find out language situation and the application of language grammar (spelling, choice of words, and sentence structure) in Ambon City primary school public area. It is a qualitative description research. Data source becomes from words on photographs which taking in elementary school environment. The analysis steps are the researcher took the picture in elementary schools; classified the picture in three groups (classrooms, teacher rooms, and school environment); and analyze the words in the pictures based on Indonesian language grammar (spelling, word choice, and sentence structure). The conclusion of this research are public elementary school in Ambon still using Indonesian language in their public space; and there are so many mistakes in application of Indonesian language grammar. The mistakes which the research founds were disobedient in using punctuation mark, chose the wrong word, and mixing Indonesian with foreign language sentence structure.